2017
DOI: 10.1002/app.45326
|View full text |Cite
|
Sign up to set email alerts
|

Microporous PDMAEMA‐based stimuli‐responsive hydrogel and its application in drug release

Abstract: The microporous hydrogels (Pn-Cm gels) composed of poly(dimethylaminoethyl methacrylate) and carboxymethylchitosan were synthesized in situ radical polymerization by using nano g-Fe 2 O 3 particles as pore-agent. The microporous structure formed through eliminating the Fe 2 O 3 particles was designed to achieve a faster response rate and better drug loading effect. Comparing to the neat gels, Pn-Cm gels exhibit deteriorative mechanical properties with the increased pores, while the gels still keep the elastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…1 b). A signal at 1169 cm −1 was attributed to the stretching vibration of the C-O moiety of the DMAEMA copolymer [ 46 ]. Additionally, the strong peaks around 2926 and 1386 cm −1 are related to the aliphatic C-H stretching and bending mode, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 b). A signal at 1169 cm −1 was attributed to the stretching vibration of the C-O moiety of the DMAEMA copolymer [ 46 ]. Additionally, the strong peaks around 2926 and 1386 cm −1 are related to the aliphatic C-H stretching and bending mode, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogel has become one of the matrix materials of microfluidic chips (Liu M. et al, 2017;Yang F. et al, 2018;Jing et al, 2019;Mofazzal Jahromi et al, 2019;Nielsen et al, 2020), which usually have a hydrophilic porous structure, and its porous structure is filled with water molecules, allowing biomacromolecules to pass through (Lee et al, 2014;Chen et al, 2016;Liu M. et al, 2017;Chen et al, 2017;Xu et al, 2019;Huang et al, 2020;Vera et al, 2021).…”
Section: Preparation Of Microfluidic Chip 21 Materials Of Microfluidi...mentioning
confidence: 99%
“…PNIPAM gels are commonly used for drug delivery, , dosimeter, , and biosensing applications. Few studies have demonstrated that it can also be used for soft-actuation purposes. , A PNIPAM gel shows several key characteristics suitable for development of a smart braille tablet.…”
Section: Introductionmentioning
confidence: 99%